2019
DOI: 10.3386/w26331
|View full text |Cite
|
Sign up to set email alerts
|

Are Small Farms Really more Productive than Large Farms?

Abstract: We revisit the long-standing empirical evidence of an inverse relationship between farm size and productivity using rich microdata from Uganda. We show that farm size is negatively related to yields (output per hectare), as commonly found in the literature, but positively related to farm productivity (a farm-specific component of total factor productivity). These conflicting results do not arise because of omitted variables such as land quality, measurement error in output or inputs, or specification issues. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is in line with previous studies that also reported that most farmers in sub-Sahara African countries are small-scale and subsistence in nature [46,84,85]. Though some studies have found small-scale farms to be more productive and efficient [86,87], others have challenged this finding, reporting that small farms are characterized by low efficiency, low productivity, and weak integration into the market [88][89][90]. This is in agreement with our study results that show that small-scale subsistence farms had the lowest milk productivity per cow, both in wet and dry seasons, and lowest household income.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies that also reported that most farmers in sub-Sahara African countries are small-scale and subsistence in nature [46,84,85]. Though some studies have found small-scale farms to be more productive and efficient [86,87], others have challenged this finding, reporting that small farms are characterized by low efficiency, low productivity, and weak integration into the market [88][89][90]. This is in agreement with our study results that show that small-scale subsistence farms had the lowest milk productivity per cow, both in wet and dry seasons, and lowest household income.…”
Section: Discussionsupporting
confidence: 92%
“…4. Additionally, total factor productivity (TFP) is commonly used to represent productivity (Sabchez et al ., 2019). Unfortunately, data on the detailed factor inputs of maize production needed to calculate TFP are unavailable in the 2015 CHFS.…”
Section: Notesmentioning
confidence: 99%
“…Formally, we introduce the concept of effective labor , namely, amount of effort per unit of working time. Due to moral hazard or other incentive‐compatibility problems (Feder, 1985; Sanchez et al., 2019), hired labor may not perform to its full efficiency. For l units of hired labor on the large farm, the effective labor input is only ωl where ω1.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Countering the viewpoint in favor of promoting small‐scale agriculture as a development strategy are arguments that the inverse productivity‐size phenomenon is largely due to measurement error, imperfect definition of productivity (Sanchez et al., 2019), or measures a relationship among only very small farms, because few farms larger than five hectares, for example, are included in datasets assembled to test the relationship (Collier & Dercon, 2014; Sheng et al., 2019). Furthermore, focusing narrowly on yields of farmland misses important disadvantages of smallholder farms in adopting quality‐enhancing skills and technology, realizing economies of scale in trading, marketing, and storage (Feder et al., 1985), and confronting various market imperfections in input and output markets.…”
Section: Introductionmentioning
confidence: 99%